2015
DOI: 10.1097/acm.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Use, Knowledge, and Beliefs About Cigarettes and Alternative Tobacco Products Among Students at One U.S. Medical School

Abstract: Purpose In the United States, the prevalence of the use of alternative tobacco products (ATPs) (e.g., hookahs, e-cigarettes, cigars/cigarillos) has increased sharply. As future health care providers, medical students will play a critical role in health promotion and disease prevention. This study investigated medical students’ use, knowledge, and beliefs about cigarettes and ATPs. Method In 2014, the authors surveyed all students enrolled at one medical school in New York City. The survey included questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 27 publications
8
54
0
1
Order By: Relevance
“…Almost 40% of participants reported lifetime hookah smoking, about 10% in the past year, and about 3% in the past 30 days. These rates are similar to those reported in the study of medical students in an urban U.S. medical school, where 43% reported ever using a hookah, 16% in the past year, and 1% in the past 30 days (Zhou et al., ). Overall, 75.8% of student nurses reported lifetime use of an ATP and 5.9% current use.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Almost 40% of participants reported lifetime hookah smoking, about 10% in the past year, and about 3% in the past 30 days. These rates are similar to those reported in the study of medical students in an urban U.S. medical school, where 43% reported ever using a hookah, 16% in the past year, and 1% in the past 30 days (Zhou et al., ). Overall, 75.8% of student nurses reported lifetime use of an ATP and 5.9% current use.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study conducted with medical students in an urban U.S. medical center found that about 4% reported current cigarette use, 4.8% currently used ATPs, and 51.7% reported lifetime use of ATPs. Students in the study consistently estimated cigarettes to be more harmful that ATPs despite the absence of research evidence comparing the two (Zhou et al., ). No studies of nurses’ use of ATPs have been published to date.…”
mentioning
confidence: 99%
“…Two hundred and fifty articles 153,192194,197,203,239,265,271,304,323326,329,332,333,335339,341344,346,348,350,351,353362,365,367369,372,374376,378381,384,388,390,393396,404406,408,414416,418,420422,425,426,432,434,436,440,441,444450,453456,459462,465,468,472,475,476,478,488,489,491,494,496498,500,502,504,506646 have been published on vaping patterns.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…20 In line with this finding, recent data indicates that even among U.S. medical school students, there is a belief that alternative tobacco products contribute less than cigarettes to various diseases. 21 Highlighting the need to understand advertising surrounding alternative tobacco products, a prior study on tobacco advertising from 2009 to 2013 indicated that cigarette magazine advertising did not influence cigarette demand while e-cigarette TV advertising did influence demand. 20 …”
Section: Introductionmentioning
confidence: 99%